2011
DOI: 10.1007/s11524-011-9577-2
|View full text |Cite
|
Sign up to set email alerts
|

Youth Physical Activity Opportunities in Lower and Higher Income Neighborhoods

Abstract: The presence of youth physical activity opportunities is one of the strongest environmental correlates of youth physical activity. More detailed information about such opportunities is needed to maximize their contributions to physical activity promotion especially in under resourced, lower income areas. The objectives of this study were to construct a comprehensive profile of youth physical activity opportunities and contrast profile characteristics between lower and higher income neighborhoods. Youth physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…In the present study, the average total number of facilities, amenities, and features per park was not significantly different across income or percent minority tertiles. These findings are similar to another study conducted in KCMO (39). However, these totals may mask inequities in the distribution of specific types of park features across neighborhoods throughout the city.…”
Section: Park Featuressupporting
confidence: 89%
“…In the present study, the average total number of facilities, amenities, and features per park was not significantly different across income or percent minority tertiles. These findings are similar to another study conducted in KCMO (39). However, these totals may mask inequities in the distribution of specific types of park features across neighborhoods throughout the city.…”
Section: Park Featuressupporting
confidence: 89%
“…This result seems to be in disagreement with ours. However, it has been suggested [ 54 ] that lower income neighborhoods provide a greater amount of government-funded opportunities for PA when compared to higher income neighborhoods. Furthermore, it needs to be acknowledged that sports activity is only one facet of overall PA, which may contribute to further explaining this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Two Scottish, 48,76 one German, 84 one US, 87 and one Danish 88 study found there to be more facilities in areas of greater deprivation.…”
Section: Number Of Recreational Facilitiesmentioning
confidence: 94%
“…The US study 87 further classified facilities as those suitable for children/adolescents or for adults, finding that the availability of facilities for children/adolescents was significantly better in neighbourhoods that were more socially disadvantaged. For adults, they found a trend towards this, but findings were not significant.…”
Section: Number Of Recreational Facilitiesmentioning
confidence: 99%